2018
DOI: 10.24136/eq.2018.034
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-criteria analysis of regional entrepreneurship conditions in Poland

Abstract: Research background: Building effective conditions for doing business and sup-porting entrepreneurs is currently considered as a basic growth determinant. It is a policy objective not only at the national level, but also an important factor influencing the competitive potential of regions and local communities. It is especially important in the case of Central European countries and regions that face the problem of closing development gap. Therefore, comparative research with regard to entrepreneurship conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…They are often led by entrepreneurs who face the challenge of simultaneously managing business decisions and their own well-being. The competitiveness of tourism destinations often depends on these entrepreneurs and therefore understanding their motivations and work pattern is crucial (Peters, Kallmuenzer and Buhalis, 2019;Rogalska, 2018). Though tourism has become a significant element influencing how people inhabit their world, the dwelling perspective as a conceptual tool has generated little interest amongst scholars studying these toured landscapes from a local perspective (Prince, 2018;Alammari,Darougi, Dunay, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…They are often led by entrepreneurs who face the challenge of simultaneously managing business decisions and their own well-being. The competitiveness of tourism destinations often depends on these entrepreneurs and therefore understanding their motivations and work pattern is crucial (Peters, Kallmuenzer and Buhalis, 2019;Rogalska, 2018). Though tourism has become a significant element influencing how people inhabit their world, the dwelling perspective as a conceptual tool has generated little interest amongst scholars studying these toured landscapes from a local perspective (Prince, 2018;Alammari,Darougi, Dunay, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Polish family firms participate in dynamic changes taking place on the market and have to face new challenges affecting their functioning and the shape of their strategy. In the aspect of progressing globalisation processes, strategic orientation directed at taking innovative actions that will enable the company to adapt to the requirements of the market economy, European integration and internationalisation are important (Wach, 2017;Rogalska, 2018;Ivanová, 2017;Korcsmáros & Šimova, 2018). At the same time, they are also subject to processes of changes resulting from their family nature connected, for example, with the processes of succession.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have demonstrated that different factors originated from within and outside organizations influence their entrepreneurial activity (Shepherd et al, 2019;Rogalska, 2018). Institutional environment is seen as a critical component in understanding the level of entrepreneurial activity (Bjørnskov & Foss, 2016;Bowen & De Clercq, 2008;Chowdhury et al, 2015;Grilli et al,2018;Stenholm et al, 2013;Yay et al, 2018).…”
Section: Introductionmentioning
confidence: 99%